Sistem Parkir Cerdas Berbasis Internet Of Things - Saiful Bahri; Deanna Durbin Hutagalung (CV. Multi Kreasi Media, 2023)
Currently parking is still operated manually, starting from cars queuing when entering the parking lot because parking attendants are still manually inputting vehicles into the system, this will cause the queue of cars to get longer at the parking entrance, especially during rush hours, then parking users are still constrained or have difficulties in finding an empty parking space, they are looking for an empty parking space by surrounding the parking area so it is less efficient and takes a very long time to park the vehicle, and it is not uncommon for parking users to forget to park their vehicle on the floor and how many blocks, this is also a separate problem for parking users because they have to search in a large area. Based on this, researchers feel the need to make an intelligent parking control device based on the Internet of Things (IOT) using an Arduino microcontroller as the controlling brain, then the micro controller will send data to the user's application server, so the user can find out which parking slots are empty and which are filled. then the user can also order the parking space through the application.